PENGEMBANGAN MODEL PEMBELAJARAN KIMIA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES SAINS SISWA SMU - Sunarya, Yayan; Rohman, Ijang; Mulyani, Sri; Anwar, Budiman (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2001)
This research develop model of teaching chemistry in senior high school to improve student thinking skill and science process skill. These skills are chosen based on characteristics of thermo-chemistry concept. There are three procedures in this research, i.e.: analysis of thermo-chemistry concepts, development of teaching model, and its implementation. The implementation carried out by the teacher. Subject of this research are 40 students of SMUN Lembang Bandung. The result of model implementation are three kinds of data, consist of teaching-learning activities, assessment test, and interview. Teaching learning activities data are analyzed by subject matter pedagogy method. The result of assessment test analyzed according to assessment type. The interview data support the teachable and accessible of the model. Model implementation by the teacher was not appropriate with the design in classroom activities. On the other hand, students have good concept achievement, but only for few indicator of the thinking skill and science process skill. Key words: thermo-chemistry, teaching model, thinking skill, science process skill